Apostolus Christinopolitanus from the 12th Century: Manuscript History and their Dialectal Features - BAKSHAEVA, Aliona Andreevna; ZHOLOBOV, Oleg Feofanovich; SOSNOWSKI, Jan (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The article presents the research of an Old Russian copy of Apostolos (The Apostolus Christinopolitanus from the 12th century, The Lviv Historical Museum of Ukraine). This article describes the manuscript history, orthographic systems, phonetic features. The study presents an analysis of regional characteristics of The Apostolus Christinopolitanus, which confirm its Galicia-Volyn origin. Despite the lingering ecclesiastical tradition, the book manuscript contains a large number of Eastern Slavic dialect elements. The linguistic parameters of the codex were analyzed for the first time. The Apostolus Christinopolitanus may have been the primary source for the Old Russian literary language of the 12th-14th centuries. RESUMEN El artículo presenta la investigación de una copia en ruso antiguo de Apostolos (El Apostolus Christinopolitanus del siglo XII, El Museo Histórico de Lviv de Ucrania). Este artículo describe la historia del manuscrito, los sistemas ortográficos, las características fonéticas. El estudio presenta un análisis de las características regionales del Apostolus Christinopolitanus, que confirman su origen Galicia-Volyn. A pesar de la tradición eclesiástica persistente, el manuscrito del libro contiene una gran cantidad de elementos del dialecto eslavo oriental. Los parámetros lingüísticos del códice se analizaron por primera vez. El Apostolus Christinopolitanus pudo haber sido la fuente principal del lenguaje literario ruso antiguo de los siglos XII-XIV.